Effect of Varying Level of Crude Protein and Energy on Insulin-like Growth Factor-I Expression Level in Indonesian Hybrid Chicken - Perdamaian, A.B.I.; Saragih, H.T.S.S.G.; Daryono , B.S. (International Journal of Poultry Science, 2016)
Objectives: The aims of this study were to investigate the effect of crude protein and energy level in feed on insulin-like growth factor-I (IGF-1) expression level in a hybrid chicken (female Layer chicken×male Pelung chicken). Methodology: To study the correlation between feed type and IGF-1 expression level. Day-old chick (DOC) hybrids were divided into four groups and each group comprised 10 individuals. First group was fed with feed A [22% Crude Protein (CP) and 3100 kcal kg–1 Metabolizable Energy (ME)], second group was fed with feed B (20% CP and 3300 kcal kg–1 ME), third group was fed with feed C (21% CP and 2800 kcal kg–1 ME) and fourth group was fed with standard feed after starving for 3 days post hatching. Chickens were observed from post-hatch to the 7th day and weighed (at 0, 3 and 7 days) and five individuals were sacrificed at the 7th day for IGF-1 analysis. Total RNA was isolated from the liver for gene expression analysis. Real-time PCR was used to study the IGF-1 expression profiles of each group after being normalized with β-actin. Results: The highest body weight was recorded for group 1, followed by group 2, 3 and 4. The IGF-1 expression level was noticeably high for feed A, B and C groups by 4.82, 3.82 and 1.9 fold, respectively, compared with the starved group. The weight highly correlated with IGF-1 expression level (R2 = 0.8). This moderate growth response to nutrition makes the hybrid chicken a suitable meat-type chicken. Conclusion: The result suggested that feed containing 22% CP and 3100 kcal kg–1 ME is a promising starter for the Indonesian hybrid chicken.